Institutional Profile: Pharmacogenomics research at Newcastle University. (September 2012) - Daly, Ann K; Veal, Gareth J; Jamieson, David; Coulthard, Sally
Newcastle University has been active in the field of pharmacogenomics/pharmacogenetics research since 1988. Research activity is based at the Faculty of Medical Sciences and is led by four professors within two separate research institutes. This article describes the various ongoing research projects and the teams involved together with our teaching activities in the subject.